Impact of Supply Chain Integration, Supplier Collaboration, and Quality Management on the Performance of Manufacturing Companies in Indonesia (Case Study of a Manufacturing Company in West Java) - Tera Lesmana (West Science Interdisciplinary Studies, 2023)
This study aims to examine the impact of supply chain integration, supplier collaboration, and quality management on the performance of manufacturing companies in Indonesia, with a particular focus on companies located in West Java. A survey was conducted on 150 manufacturing companies, and the data were analyzed using quantitative methods. The results showed that these three factors positively and significantly impacted the company's performance. In particular, supply chain integration substantially affects company performance, followed by supplier collaboration and quality management. These findings have important implications for supply chain management practices in Indonesia's manufacturing sector.